Prevalencia especies del género cándida en pacientes portadores de aparatología ortopédica revisión de la literatura (2020)
Adhesion and colonization of C. albicans is the initial step for oral candidiasis, C. albicans is the most frequent species to alter the oral ecological contour, the presence of removable orthopedic appliances can increase the presence of yeast species. The internal surfaces of removable dentures or removable orthotics that contact palatal tissues function as reservoirs for microorganisms. OBJECTIVE: To determine the prevalence of species of the genus candida in patients with orthopedic appliances, through a bibliographic review. METHODOLOGY: A literature review was carried out to identify and summarize all the publications related to the prevalence of C. albicans in patients with orthopedic appliances. The literature review was carried out using search engines such as Scielo, Pubmed, Google Scholar, BMC Oral, RESULTS: candida species are frequently found in the oral cavity, with a colonization percentage of up to 60% in young adults. These percentages vary from individual to individual and according to geographic location. CONCLUSIONS: The most frequently isolated species turned out to be C. albicans, it is not the only one related, other species were isolated such as Candida non albicans, C. tropicalis, C. krusei, C. glabrata, opportunistic yeast microorganisms related to the presence of orthopedic appliances